MAXIMAZING TEACHER ROLES IN SHAPING SELF-DIRECTED LEARNERS - Agustiani, Indah Windra Dwie (English Community Journal, 2019)
This paper attempts to offer some efforts that can be applied or employed by teachers  in teaching learning activities to shape self-directed learners. It encompasses some theories about roles of teachers, roles of learners, the definition and characteristics of self-directed learners,the advantages of self-directed learning, and some possible tips of shaping self-directed learners. Some roles of teachers  are discussed in this paper to highlight that  teachers do not only teach and give some materials to be learned by their  learners but have great tasks, like  to be  a monitor of students learning, motivator, organizer, and controller of pupil behaviour,provider of accurate language models,counselor and friend, needs analyst,material developer, and evaluator (Richard :1990:4). Hence, a teacher must encourage learners to take on greater degree of responsibility for their own successful learning (Hedge, 2000:34) and a teacher must motivate and help the learners to gain and develop the executive control of their  learning strategies especially metacognitive strategies to teach them how to learn (Joyce,etal:  2009:16).Thus, some roles of learners become important to be included in this paper to assert that the burden of learning cannot be merely puored on the teacher but the learners  have some roles need to be contemplated for the success of teaching and learning.  Therefore, the integration of teacher - learner  awareness toward their roles in teaching learning process can be effectively shaped to generate self-directed learners.